The sources of Ibn Tulun's soffit decoration - Azab, Pamela Mahmoud (AUC Knowledge Fountain, 2015)
Ornamental decoration has been studied extensively by various art historians who have provided a multitude of interpretations for the underlying reasons behind the use of different ornaments as well as the influence different eras had on the design of ornament. Stucco played an important role as a decorative element used throughout the ages; it is considered an inexpensive way of decoration as well as a speedy one. Stucco decoration was also perceived by some to convey special meaning and has been analysed from an architectural as well as a geometrical perspective. This thesis proposes to examine the source of the stucco decoration of the mosque of Ibn Tulun’s soffits according to their pattern. Some previous scholars have attributed them to Byzantine sources, others to Abbasid Samarra. This study will attempt to determine where the closest parallels lie. It will also trace the origins of the patterns, examining the question of whether the Samarra patterns are completely original, or whether they in turn are indebted to Byzantine or Roman prototypes.